Feminism in Patriarchal Society Reflected in the Main Characters in Sabrina & Corina - Panggabean, Gloxzy Ruth; Gultom, Feriyanti Elina (Universitas Negeri Medan, 2024)
This study deals with feminism in patriarchal society based on the main character in anthology of short story named Sabrina & Corina by Kali Fajardo-Anstine. This research used qualitative descriptive as the method. The data of this study were dialogue and narratives that appeared in the story. The data was analyzed using Hannam™s (2007) theory. It was found that there are three definition of feminism found in the data, they are: 1) Recognition of imbalance power